Efektivitas Deferasirox pada Pasien Thalasemia Mayor: Artikel Review: Efficacy of Deferasirox for Thalassemia Mayor: Review Article - Naksa Garnida Arfie; Bambang Subakti Zulkarnaen; Sudarmanto Sudarmanto (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Thalassemia is a heterogeneous grouping of genetic disorders resulting from decreased synthesis of the alpha or beta chains of hemoglobin. Anemia and iron overload are the main causes of morbidity and mortality due to thalassemia disease. Iron chelation has improved the survival and quality of life of patients with thalassemia major. Deferasirox (DFX) was developed as monotherapy for the treatment of transfusion iron overload. Search data in this literature study using an electronic database, namely Science Direct, Pubmed with the keywords thalassemia, deferasirox and efficacy. The search results obtained 1015 articles and 5 articles that matched the inclusion and exclusion criteria. The total patients in this study were 410 people from 5 countries. The results of the review article found that deferasirox was effective in reducing iron in the body as seen from the LIC (Liver Iron Concentration), T2* heart and serum ferritin in patients with thalassemia major.